Sedimentary dykes and genetically related features in the Upper Jurassic Jhuran Formation of the Kachchh Rift Basin, Western India - Fursich, Franz T.; Alberti, Matthias; Pandey, Dhirendra K. (Journal of the Palaeontological Society of India, 2022)
In the Kimmeridgian-Tithonian Jhuran Formation of the Kachchh Rift Basin features such as sedimentary dykes, convolute bedding, and intraformational pillows are documented at several levels and localities. They are interpreted as having been produced by seismic events. Together with features, such as local intraformational unconformities and dying growth faults recorded earlier on in the literature they indicate that the basin was in a syn-rift stage until the end of the Jurassic. Interestingly, signs of seismic activity in the basin are far more conspicuous during the Oxfordian - Tithonian time interval than during the Middle Jurassic.
CRIS-Team WoS Importer:2023-02-10